(untitled) (Journal of history, 2024)
Introduction. The introduction of the "Provisional Regulations of 1868", "Regulations of 1891" and other normative acts concerning the Kazakh lands marked the start of certain reforms. In historiography, minimal attention is paid to the formation and mission of the institute of county chiefs in the imperial administrative system of the Steppe Region. This study is designed to fill in the "white spots" of the designated scientific problem. The purpose and objectives of the study are to make an attempt on the basis of archival sources and published publications to summarize the specifics and mechanisms of the activities of county chiefs as "guides" of the evolution of the administrative apparatus in the Kazakh lands in the second half of the XIX - early XX centuries. The materials used in the study were identified from the funds of the Central State Archive of the Republic of Kazakhstan, The Russian State Historical Archive. For the first time, sources in the Kazakh language from the first Kazakh-language magazines and newspapers of the early twentieth century are introduced into scientific circulation. The methodology of research is: analysis and synthesis, induction and deduction, content analysis, comparative, etc. Results. The article analyzes the sources on the activities of the district chiefs of the Steppe region. An attempt is made to draw attention to the specifics of the functioning of the institute of county chiefs, at times of aggravation of the socio-political situation in the region. Conclusion. In the designated chronological period, the district chiefs faced protest movements, they were involved in a confrontation with Kazakh leaders. Thus, the institution of county chiefs was a priori founded as apologists for the colonial system. The practical significance of the results of the study is seen in the generalization of the historical experience of managing the territories of forest-steppe spaces of Kazakhstan. Key words: empire, Russia, Kazakhs, county chiefs, protests, steppe, management.